(untitled) (Revista Venezolana de Salud Pública, 2018)
A descriptive, cross sectional study was carried out to examine the enteroparasite contamination of 300 banknotes of the six denominations that circulate in the Barquisimeto-Cabudare urban axis (2,5,10,20,50 and 100 BsF), through the washing of each with 100 ml of water with 20% Tween 20 for 5 minutes each side and with the aid of a sterile brush, this volume was placed in two, plastic centrifuge tubes (clean) allowed to decant for two hours , Then centrifuged at 3000 rpm for 10 minutes to observe the pellet with saline and lugol with 100X and 400X magnification. An abundance of enteroparasites was obtained in contaminated banknotes of 29% (87/300), with a diversity of four taxa. Blastocystis sp. (68 of 87 contaminated), Endolimax nana (16/87), Giardia sp. (2/87) and Entamoeba coli (1/87); Banknotes with less denomination were more contaminated than those with the highest denomination and 96,6% of the contaminated banknotes were dirty, while only 3,4% of the contaminated banknotes were clean or new banknotes. No helminth eggs were observed. It is concluded that tickets in this area are an important element (fomites) in the direct transmission of intestinal protozoa from one person to another.